When Aunt Mattie got her wings - Mathers, Petra (Lottie, 2014)
When Aunt Mattie dies, best friends Lottie and Herbie console each other and celebrate Aunt Mattie's life by scattering her ashes and preparing her favorite snack--peanut butter and jelly sandwiches (with bananas).